2019
DOI: 10.3892/ol.2019.11165
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of TXNIP predicts poor prognosis in patients with clear cell renal cell carcinoma

Abstract: Accumulating evidence has demonstrated that thioredoxin interacting protein (TXNIP) is abnormally expressed in a variety of malignant tumors and functions as a tumor suppressor. However, the association between TXNIP and clear cell renal cell carcinoma (CCRCC) has not yet been fully elucidated. The aim of the present study was to evaluate the role of TXNIP in CCRCC using The Cancer Genome Atlas (TCGA) database. The RNA sequencing data and corresponding clinical data were collected from TCGA database. The assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…TXNIP was commonly silenced in cancer cells due to genetic or epigenetic events [44]. In addition, a recent study revealed that downregulation of TXNIP could predict worse survival in KIRC, which is in good accordance with our results [45]. Regarding APP, current studies have demonstrated its overexpression and characteristic of oncogenes in some malignancies such as breast cancer [46], pancreatic cancer [47], and NSCLC [48].…”
Section: Discussionsupporting
confidence: 90%
“…TXNIP was commonly silenced in cancer cells due to genetic or epigenetic events [44]. In addition, a recent study revealed that downregulation of TXNIP could predict worse survival in KIRC, which is in good accordance with our results [45]. Regarding APP, current studies have demonstrated its overexpression and characteristic of oncogenes in some malignancies such as breast cancer [46], pancreatic cancer [47], and NSCLC [48].…”
Section: Discussionsupporting
confidence: 90%
“…In contrast, TXNIP , a member of the tumor suppressor family, has been shown to increase p53 stability and activity, thereby sensitizing breast cancer cells to apoptotic stimulation [ 48 ]. On the other hand, a recent report showed that an increased level of TXNIP probably results from the activation of the JAK-STAT pathway and is associated with a favorable prognosis in patients with renal cell carcinoma [ 49 ]. In this study, our data showed that FOXD1 knockdown dramatically enhances the expression of TXNIP and the IFN-α/γ responsiveness, which is determined by the interaction of the JAK/STAT1 signaling axis with IFN-stimulated response element (ISRE) and IFN-gamma activation site (GAS) response element within the upstream promoter of the luciferase gene in oral cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The stress response gene ATF3 , has been shown to activate erastin-induced ferroptosis by repressing amino acid antiporter system Xc – ( Wang et al, 2020 ) and could serve as a prognostic biomarker in hepatocellular carcinoma ( Li et al, 2021 ). TXNIP has been implicated in ferroptosis in retinal cells ( Singh et al, 2020 ), and its downregulation indicates poor prognosis in patients with clear cell renal cell carcinoma ( Gao et al, 2020 ). Furthermore, ABCC1 , also known as multidrug resistance protein 1 ( MRP1 ), was confirmed to affect ferroptosis process by mediating GSH efflux ( Cao et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%